An overview of approaches to transition finance for hard-to-abate sectors - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2023)
Climate finance has witnessed significant growth as a burgeoning field of long-term finance globally in recent years. However, it has yet to reach the necessary scale for mobilizing sufficient funds to support the decarbonization efforts of businesses. This shortfall is partly attributed to ongoing investors' concerns about greenwashing risk. Many global companies have made commitments to achieve the net-zero target by 2050, but without consistent short-and medium-term targets, comprehensive data and progress report, and detailed action plans. While the Task Force on Climate-Related Financial Disclosure (TCFD) recommendations have contributed to advancing disclosure frameworks, the standardization of corporate disclosures has not made substantial progress. Furthermore, a series of initiatives-such as the environmental, social, and governance (ESG) ratings offered by data providers, the certification of green or sustainability-linked bond labels through second-party opinions, as well as various taxonomies for green activities-have enhanced transparency to some extent but their divergent approaches have hampered climate finance from expanding further. The recent effort to standardize climate-related disclosures by the International Sustainability Standards Board (ISSB), which was established by the Trustees of the International Financial Reporting Standards (IFRS) Foundation, is a positive development, but broader initiatives are required to promote climate finance. In particular, transition finance in hard-to-abate sectors (such as steel, chemicals, cement) remains underdeveloped, despite the urgent need to financially support their emissions-reducing efforts. This paper provides an overview of various approaches toward transition finance intended to enhance credibility while addressing their challenges.
Keywords: G15; G32; Q01; Q54; 330; transition finance; carbon budget; hard-to-abate sectors; ISSB Climate-Related Disclosures; taxonomy; traffic-light classification system